2020
DOI: 10.3390/ijms21072619
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of MicroRNAs Expression in Regulation of Extracellular Matrix and Other Drug Resistant Genes in Drug Resistant Ovarian Cancer Cell Lines

Abstract: Ovarian cancer rates the highest mortality among all gynecological malignancies. The main reason for high mortality is the development of drug resistance. It can be related to increased expression of drug transporters and increased expression of extracellular matrix (ECM) proteins. Our foremost aim was to exhibit alterations in the miRNA expression levels in cisplatin (CIS), paclitaxel (PAC), doxorubicin (DOX), and topotecan (TOP)-resistant variants of the W1 sensitive ovarian cancer cell line-using miRNA micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 119 publications
(156 reference statements)
2
28
0
Order By: Relevance
“…As an initial effort to understand the potential involvement of hsa-miR-105 in paclitaxel resistance, we examined the expression of hsa-miR-105 in a microRNA profiling microarray expression dataset consisting of three pairs of parental EOC cells and their PTX-resistant sublines (GSE148251) ( 20 ). Student's t-test demonstrated that the expression of hsa-miR-105 was significantly downregulated in PTX-resistant sublines compared to their parental cell lines (percentage decrease >78.8%, P<0.0001, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an initial effort to understand the potential involvement of hsa-miR-105 in paclitaxel resistance, we examined the expression of hsa-miR-105 in a microRNA profiling microarray expression dataset consisting of three pairs of parental EOC cells and their PTX-resistant sublines (GSE148251) ( 20 ). Student's t-test demonstrated that the expression of hsa-miR-105 was significantly downregulated in PTX-resistant sublines compared to their parental cell lines (percentage decrease >78.8%, P<0.0001, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A microRNA profiling microarray expression dataset consisting of three pairs of parental EOC cells and their PTX-resistant sublines (GSE148251) ( 20 ) was downloaded from Gene Expression Omnibus (GEO platform). The miRNA expression levels were analyzed using GEO2R bioconductor project and provided as log2 ratios ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Maintaining the structural integrity of the arteries, uterus, and intestine is the main function of COL3A1. COL3A1 is negatively regulated by miR-29a, and a regulatory relationship is thought to be associated with the resistance of ovarian cancer cell lines to topotekan [34]. As a new translocation partner gene of PLAG1, COL3A1 could be used to distinguish lipomas by affecting PLAG1 rearrangement and overexpression [11].…”
Section: Discussionmentioning
confidence: 99%
“…We screened the gene chip data by using the Gene expression omnibus (GEO, http://www.ncbi.nlm.nih.gov/geo ) database [ 14 ]. Cisplatin resistant ovarian cancer public gene expression data sets (GSE58470 and GSE45553) and miRNA expression data sets (GSE58469 and GSE148251) were selected and downloaded from GEO, with the keywords “ovarian cancer” and “cisplatin resistant” [ 15 17 ]. The GSE58470 and GSE45553 datasets, which are two mRNA datasets, contain 2 ovarian cancer cell lines (IGROV-1, OVCAR-8) and 14 samples, including 7 cisplatin resistant cell samples and 7 parental cell samples.…”
Section: Methodsmentioning
confidence: 99%